Emerging TPACK & Digitalization in Education for Sustainable Development: Voices of Secondary Education Teachers - Setoningsih, Dian Asmi (Universitas Muhammadiyah Malang, 2023)
One of the frameworks used nowadays to incorporate technology into the teaching and learning process is technological pedagogical and content knowledge (TPACK). The investigation of teachers' TPACK, specifically their comprehension, process, and obstacles in a classroom context, has not received much research, though. In order to better understand TPACK and digitalization in the secondary education classroom, this study will examine it from the viewpoints of teachers. The information was gathered from three teachers who were at Thursina IIBS Malang, East Java, Indonesia. The study's methodology included a qualitative study. The researchers used a triangulation of data sources, including interviews, observations, and documents, to collect their responses. The verbatim transcriptions of the interviews data were followed by a thematic analysis. The results of the current study reveal four key issues, including teachers' understanding of TPACK, the acquisition of TPACK, teacher perceived level of digital literacy and teachers' challenges with TPACK. The teachers utilized a variety of ways to acquire TPACK, and they had different perspectives on TPACK. However, applying TPACK presented many benefits for the teachers. The results of this study may have an impact on how teachers should proceed with their professional development.